(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Indoor navigation within large shopping malls is often challenging due to complex layouts and lack of proper guidance systems. Visitors frequently struggle to locate stores, restrooms, exits, or other facilities efficiently. Traditional navigation methods such as static maps and signboards are often insufficient and confusing. This paper proposes MallPath, an intelligent indoor navigation system designed to assist users in navigating malls and accurately. The system utilizes digital mall maps, real-time location tracking, and pathfinding algorithms to guide users to their desired destinations. The proposed system provides floor-wise navigation, shop categorization, and shortest path suggestions. It enhances user experience by reducing time, improving accessibility, and offering an interactive interface. The solution is scalable and can be implemented in modern smart malls.